INNOVATIVE LOCAL WISDOM–BASED E-HANDOUT FOR TEACHING INDONESIAN CULTURAL DIVERSITY - Ridha Nur Azizah (Universitas Negeri Medan, 2025)
This development is motivated by the lack of knowledge of children on local wisdom in their own area, in addition to introducing local wisdom in the development area, this development also aims to find out the development of science teaching materials for grade 4 science material at Al- Hikmah Sugihwaras Islamic Elementary School. As well as to find out the validation of the feasibility of the teaching materials that have been developed in the story material about my area for class 4 The researchers used the research method R&D (research and development). This type of research refers to development research with the ADDIE Method, This type of research refers to development research.. This method consists of five stages, namely analyze, design, development, implementation, and evaluation. The teaching materials developed are E-Handouts based on local wisdom for class IV science subjects. This media can be used both in online and face-to-face learning. 2. E-Handout teaching materials based on local wisdom on Indonesian Cultural Diversity material have gone through the validity test stage of 3 experts. Test the validity of teaching materials to get a percentage of 92.5% and declared very feasible to use. Next is the validity test from the linguist, in this validity test the E-Handout teaching material gets a percentage of 97.5% and is declared very feasible to use. Then test the validity of the material experts who get a percentage of 100% and are declared very feasible to use. So it can be concluded that the E-Handout teaching materials that have been developed by researchers are very interesting and can help students introduce the local wisdom of their area, namely the Bojonegoro area